2009
DOI: 10.1152/ajpcell.00185.2009
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-mediated ERK phosphorylation and apoptosis in vascular smooth muscle cells requires GPR 30

Abstract: Recent studies suggest that the rapid and nongenomic effects of estradiol may be mediated through the G protein-coupled receptor dubbed GPR30 receptor. The present study examines the role of GPR30 versus a classical estrogen receptor (ERalpha) in mediating the growth regulatory effects of estradiol. GPR30 is readily detectable in freshly isolated vascular tissue but barely detectable in cultured vascular smooth muscle cells (VSMC). In freshly isolated aortic tissue, estradiol stimulated extracellular signal-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
111
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 41 publications
7
111
0
2
Order By: Relevance
“…4C). These results are consistent with previous studies showing that estrogen induced ERK1/2 phosphorylation via GPER/ GPR30 (1,43). The observed effect of G-1 to inhibit PMCA activity via tyrosine phosphorylation of the pump is quite consistent with previous studies demonstrating a clear inhibitory role of phosphorylation of Tyr-1176 on PMCA4b activity (34,44,45).…”
Section: Discussionsupporting
confidence: 93%
“…4C). These results are consistent with previous studies showing that estrogen induced ERK1/2 phosphorylation via GPER/ GPR30 (1,43). The observed effect of G-1 to inhibit PMCA activity via tyrosine phosphorylation of the pump is quite consistent with previous studies demonstrating a clear inhibitory role of phosphorylation of Tyr-1176 on PMCA4b activity (34,44,45).…”
Section: Discussionsupporting
confidence: 93%
“…30 In contrast, E2 acting via GPER was proapoptotic. However, the in vivo implications of these receptor-specific opposing effects of estradiol on growth regulation have yet to be established.…”
Section: November 2016mentioning
confidence: 99%
“…This synthetic phenotype is more similar to the phenotype of VSMCs maintained in primary culture, 35 the model in which we have initially characterized the role of GPER versus ERα in regulating growth. 30 Previous studies have suggested an important role of estrogen in the response to vascular injury 36 including inhibition of neointimal proliferation 37,38 and inhibition of the adventitial inflammatory response. 39,40 It has been suggested that the primary estrogen-mediated response occurred via ERα activation.…”
Section: November 2016mentioning
confidence: 99%
See 2 more Smart Citations